- - Rovaletti, María Lucrecia (Acta Bioethica, 2000)
In the presence of the problems posed by new technologies, traditional medical ethics is not able to respond satisfactorily. At the present time, research and biotechnological experimental applications are more and more numerous and artificial, following a desire and a constancy that ignores limits and whose unbalanced condition or meta-stability constitutes its unique and tireless motive. The search for knowledge vanishes in front of the implacable "logic of efficacy". This problem becomes worse because present biological revolution (Bernard), in contrast to therapeutical revolution -which affected the medical practice related to the individual- affects humanity as a species. But, wouldn't the control of scientific activities be equivalent to restrict the acquisition of fundamental knowledge? To new domains correspond new responsibilities. Opposite to the old humanism founded on finality and paternalism, a new humanism appeals to responsibility. Thus, the "principle of responsibility" (Hans Jonas) has an ethical sense only when each individual discovers himself as author, in one sense or the other, of long-range changes and of forces he does not control. In a time in which science has become more operative, active and manipulative -that is to say where knowledge is also power and acting- philosophical thinking has to be directed to a new Practical Reason.